Implementasi Kurikulum Merdeka di Kelas X-2 SMAN 22 Surabaya dengan Menggunakan Metode Understanding by Design - Sunani Sunani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Merdeka Curriculum provides flexibility in the implementation of education. Understanding by design become one of learning model that can be implemented in class. The purpose of this research is to find out the effect of implementation of understanding by design model in the Merdeka Curriculum at X2 Class, SMA Negeri 22 Surabaya. This research uses classroom action and quantitative descriptive approach. The results of the study show three major points, 1) teacher competence increased by 52% to 66,36%, 2) students activities increased by 62,74% to 75,36%, 3) learning result increased by 62,74% to 75,36%.